EFFORTS TO IMPROVE MATHEMATICAL LEARNING ACTIVITIES USING THE THINK PAIR SHARE (TPS) COOPERATIVE LEARNING MODEL IN CLASS VII - Dwi Suryaningsih; Romelan Hamzah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Student learning activities in mathematics are still not good. This is indicated by the small number of students who are actively involved in the learning process, for example, when the teacher asks questions. This study aims to improve mathematics learning activities using cooperative learning models Think Pair Share in classVIIstudents of State Junor High School (SMPNegeri) 1 Imogiri Bantul 2018/2019 academic year. This study is a classroom action research conducted in even semester of class VII B. This research is conducted in two cycles, where each cycle consists of action planning, implementation, observation, and reflection. Data collection techniques are in the form of observations, interviews, and field notes. The research instruments used are observation sheets, interview guidelines, and field notes. While the research instrument test conducted is the validity test. The data analysis technique uses a descriptive qualitative technique. Â The results showed that Think Pair Share's cooperative learning model could improve students' mathematics learning activities in class VII B in SMP Negeri 1 Imogiri Bantul. This is evidenced by the results of the observation sheet in each cycle that increased significantly. The average percentage of student activities in cycle 1 is 57,48% with satisfactory criteria. After that, the percentage in the second cycle increased to around 74,92%, indicating good criteria.